Factors Affecting the Meaning in Life of Teachers - Suyatno; Pambudi, Dholina Inang; Amurdawati, Ganis; Wantini; Ningrum, Mei Vita Romadon (Pedagogika, 2020)
This study aims to investigate the various models that affect the meaning in life of teachers. This is a quantitative study with data randomly obtained from a sample of 100 teachers at East Kalimantan, Indonesia. The results showed that self-actualization and self-transcendence are crucial factors which have an impact on the meaning in life of teachers. The policy makers need to utilize the results from this study to design various programs and training for the development of meaning in life of teachers.